ESTIMATIVA DA RUGOSIDADE SUPERFICIAL DO SOLO EM DIFERENTES CONDIÇÕES DE CULTIVO - SOUZA, Carlos Henrique Martins; PANACHUKI, Elói; RODRIGUÊS, Sonia Armbrust; LOPES, Julia Torres (ANAIS DO ENIC, 2017)
-